State of the climate in 2016 - Aaron-Morrison, Arlene P.; Ackerman, Steven A.; Adams, Nicolaus G.; Adler, Robert F.; Albanil, Adelina; Alfaro, Eric J.; Allan, Rob; Alves, Lincoln M.; Amador, Jorge A.; Andreassen, L. M.; Arendt, A.; Arévalo, Juan; et al. (2017)
In 2016, the dominant greenhouse gases released into Earth's atmosphere-carbon dioxide, methane, and nitrous oxide-continued to increase and reach new record highs. The 3.5 ± 0.1 ppm rise in global annual mean carbon dioxide from 2015 to 2016 was the largest annual increase observed in the 58-year measurement record. The annual global average carbon dioxide concentration at Earth's surface surpassed 400 ppm (402.9 ± 0.1 ppm) for the first time in the modern atmospheric measurement record and in ice core records dating back as far as 800000 years. One of the strongest El Niño events since at least 1950 dissipated in spring, and a weak La Niña evolved later in the year. Owing at least in part to the combination of El Niño conditions early in the year and a long-term upward trend, Earth's surface observed record warmth for a third consecutive year, albeit by a much slimmer margin than by which that record was set in 2015. Above Earth's surface, the annual lower troposphere temperature was record high according to all datasets analyzed, while the lower stratospheric temperature was record low according to most of the in situ and satellite datasets. Several countries, including Mexico and India, reported record high annual temperatures while many others observed near-record highs. A week-long heat wave at the end of April over the northern and eastern Indian peninsula, with temperatures surpassing 44°C, contributed to a water crisis for 330 million people and to 300 fatalities. In the Arctic the 2016 land surface temperature was 2.0°C above the 1981-2010 average, breaking the previous record of 2007, 2011, and 2015 by 0.8°C, representing a 3.5°C increase since the record began in 1900. The increasing temperatures have led to decreasing Arctic sea ice extent and thickness. On 24 March, the sea ice extent at the end of the growth season saw its lowest maximum in the 37-year satellite record, tying with 2015 at 7.2% below the 1981-2010 average. The September 2016 Arctic sea ice minimum extent tied with 2007 for the ...